The Canadian Experimental Camera-Child - Czernis, Loretta (Cinémas)

(untitled) (Cinémas, 1991)
Experimental film is not highly visible but it has had an impact on cinema as both art and technique. Conceptual and technical experiments in film take many forms depending on their cultural contexts. Canadian experimental filmmakers have recorded our inability to invent ourselves as they imagine that we might have been. They are influenced by European and American avant-garde filmmakers and their relationship to the camera as a "living" and technological entity.